DIALOGUE JOURNALS AS A COLLABORATIVE LEARNING TECHNIQUE (CoLT) FOR TEACHING WRITING - Janah, Miftahul (STKIP Muhammadiyah Pringsewu, 2018)
Learning writing is useful not only for developing studentsâ writing skill but also for improving their English skills. This study was intended to know that Dialogue Journal is effective to teach writing. This study is a quasi-experimental. Based on the data analysis, it was found that in pre-test, there were 20 % students who active in group activity and 23 %Â got excellent to very good score. Meanwhile, in post-test, the students who got excellent to very good score were 43%, and 73% students were active in group activity. It indicates that Dialogue Journal is effective to teachÂ writing.